The Epic X Camp Trainees’ Perceptions of Their Pedagogical Competence in Teaching English - Yulin Sulistyani; Andi Julian; Iftinan Rose Putri Safana; Nazelya Puspita Kencana (JEELS (Journal of English Education and Linguistics Studies), 2024)
This study aimed to know the Epic X camp trainees' perceptions of their pedagogical competence in English teaching before and after the training. The researchers analyzed the pedagogical competence concept by using Voss et al. (2011). The instruments of this study were interviews and observations of 30 trainees from the American Corner Epic X camp 2024 held by the U.S. Embassy's Regional English Language Office (RELO). They consisted of preservice teachers, in-service teachers, and postgraduate students. The result showed that the participants had positive perceptions of the practice and a better understanding of the components of pedagogical competence in terms of the lesson plan, teaching strategy, teaching method, and the most visible classroom management. The positive perception was proven by the personal interview with the participants after and before the Epic X camp program and observation during micro-teaching in Epic X camp activities. This positive perception was in line with the purpose of the Epic X camp program which empowers trainees in their competence in teaching English. The researchers recommend that such a program be implemented for English teachers in Indonesia.